(untitled) (Fiep Bulletin - online, 2016)
This work aims at presenting the motor profile of the practitioners of the participating students COPAME Project. The motor profile of each individual practitioner was drawn according to Motor Development Scale described in the Manual of Motor Assessment. The project goal is to promote recreational and recreational and water activities such as games, music with dynamic, symbolic games, sensory-motor and game rules, to an improvement of motor development of children. What kind of research was qualitative description. The sample consisted of 26 students, of both sexes, aged between 3 and 12 years, participants of the Project COPAME - extension project at the University of Santa Cruz do Sul (UNISC) ??Tests were carried out with the aid of Kit (EDM Scale Motor Development). For data analysis, the EPI-INFO software, version 6.0 (Fernádez Merino, 1996) was used, aiming to evaluate the motor patterns of the sample. In thin Motricity, the results showed deficits in global motor function assessed had the results in the global motor function evaluated showed satisfactory results and lower your age, since in equilibrium the best results were presented. Body schema / Quickness showed unsatisfactory results in comparing the number of children studied. In Spatial Organization obtained inferior results to normal and the latter evaluated Language / Temporal Organization was the test where the results showed a higher deficit. Thus, according to this study, where students were assessed individually, so one can trace an individualized treatment.